Юридичні клініки - вагома складова інституту безоплатної правової допомоги в Україні - Чернега, А.П. (Часопис Київського університету права, 2009)
В статье идет речь о формировании института бесплатной правовой помощи в Украине на современном этапе развития государства и права, а также роли юридических клиник в осуществлении такой помощи. Ключевые слова: бесплатная правовая помощь, юридическая клиника, незащищенные слои населения, малообеспеченные, офисы общественной защиты, общественные приемные, интересы граждан. The article highlights the process of forming free legal assistance institution in Ukraine at the current stage of state and law development. The paper also points out the role of the legal clinic in providing such assistance. Key words: free (of charge) legal assistance; judicial clinic; law clinic; non-defended population layers; come population layers; civil defense offices; civil receptions; citizen interests.